Firm debt structure and firm size: A micro approach - James P. Gander (The University of Utah, Department of Economics, 2010)
Micro industrial firm panel data on short-term and long-term borrowing (term debt structure) for annual and quarterly time periods over the years 1995-2008 are used to test an insulation hypothesis and a related volatility hypothesis. The former test uses a regression model relating the ratio of accounts payable in trade to long-term debt to firm size and other variables. The focus is on a micro perspective of the firm's response to the FED's monetary policy. If differs from an earlier macro perspective that focused on the existence of bank lending channels. The latter hypothesis uses the panel heteroscedastic variances recovered from the first testing procedure to test for a quadratic-form risk function (either U-shaped or inverted U-shaped) using sigma squared and the coefficient of variation as risk indexes and firm size as a determinant. The findings suggest that there is some evidence that firms do insulate themselves from the effects of monetary policy and that retained earnings have a significant role in the insulation effect. The evidence also suggests that the risk index, the variances, is related to firm size by a Ushaped quadratic function. As firm size increases, not only does the term-structure ratio fall, but the volatility falls and at a falling rate of change, approaching zero for a sufficiently large firm.
Keywords: C33; E44; E52; 330; firms; debt-structure; monetary policy